Prevalence of otomycosis in the district hospital IV of Bamako, Mali - Baba, Sacko Hamidou; Aminata, Kodio; Dicko, Abdoul Razak; Gadi, Timbine Lassina (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Otomycosis is more and more found in chronic suppurative otitis media (CSOM), several factors (iterative antibiotic therapy, self-medication, general chronic diseases, climate), may explain this phenomenon which makes it more complex to start an adequate therapy. Objective was to highlight the place of otomycosis in chronic purulent otorrhea of the middle ear in tropical settings. Study settings were like the ENT unit of the reference health centre of commune IV of the district of Bamako, the Rodolphe Mérieux laboratory. Methods: We identified the bacteriological samples taken in our unit between February 2009 and February 2018. The study involved 178 samples from a number of patients estimated at 148 with chronic purulent otitis media. All samples collected were transported and evaluated by both direct microscopic examination and culture method for bacteria and fungi examination, which were identified by standard procedures. Results: The female sex predominated with 60.82%. The mean age of the patients was 27 years (range 5 months to 91 years). Among 170 samples, 36.19% yielded fungal growth, 59.7% grew bacteria and 50.94% showed mixed growth of fungi and bacteria. Major fungal isolates were candida species (n=38). 21 isolates were identified as Aspergillus. Conclusions: This study will have made it possible to confirm the significant place of otomycosis in the chronic suppurative pathology of middle ear in our structure, requiring its consideration in the adequate treatment of CSOM.